2018
DOI: 10.1111/mpp.12622
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance in the rice cultivar Manikpukha to the rice stem nematode Ditylenchus angustus

Abstract: The incompatible interaction between the rice cultivar Manikpukha and the rice stem nematode Ditylenchus angustus has been reported recently. This research focuses on the underlying mechanisms of resistance in Manikpukha. Invasion, post-infection development and reproduction of D. angustus were compared in compatible and incompatible interactions to identify the stage in which resistance occurs. The results indicate that resistance in Manikpukha is associated with reduced development and reproduction, implying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 74 publications
2
12
1
Order By: Relevance
“…The fact that the PAL genes, considered as the starting point of the phenylpropanoid pathway, are often up-and down-regulated in resistant and susceptible interactions, respectively, shows that phenylpropanoids are important defence molecules. This was shown in several plant-pathogen interaction experiments (Gao et al, 2008;Uehara et al, 2010;Feng et al, 2011;Khanam et al, 2018). In contrast to our observations, Djamei and colleagues (2011) reported an increase in phenylpropanoid biosynthesis products in plants infected with U. maydis, which indicates that chorismate is directed into the phenylpropanoid pathway.…”
Section: Discussioncontrasting
confidence: 98%
“…The fact that the PAL genes, considered as the starting point of the phenylpropanoid pathway, are often up-and down-regulated in resistant and susceptible interactions, respectively, shows that phenylpropanoids are important defence molecules. This was shown in several plant-pathogen interaction experiments (Gao et al, 2008;Uehara et al, 2010;Feng et al, 2011;Khanam et al, 2018). In contrast to our observations, Djamei and colleagues (2011) reported an increase in phenylpropanoid biosynthesis products in plants infected with U. maydis, which indicates that chorismate is directed into the phenylpropanoid pathway.…”
Section: Discussioncontrasting
confidence: 98%
“…Many genes involved in plant secondary metabolism, such as phenylpropanoid, lignin and flavonoids, were affected after nematode infection . The phenylpropanoid or lignin pathway and its products play important roles in the incompatible interaction and cultivar resistance against nematodes . Compared with R155, all 19 DEGs involved in phenylpropanoid (7 DEGs) or lignin (12 DEGs) metabolism were significantly up‐regulated in the uninfected roots of Jiabali (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of OsPAL1 (Os02g0627100) was up‐regulated 1.43‐fold compared with that of R155. In the rice‐resistant cultivar Manikpukha, OsPAL1 plays a pivotal role in resistance to the rice stem nematode Ditylenchus angustus , and the lignin content significantly increased after the nematode infection . That showed that rice resistance to the nematode partially relied on the metabolism of phenylpropanoid or the biosynthesis of lignin.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, silencing of the chalcone synthase gene increases lignin deposition in wheat (Eloy et al, 2017). Activation of the phenylpropanoid biosynthesis pathway may also be involved in the production of anti-PPN secondary metabolites (Khanam et al, 2018). For example, transcinnamaldehyde is a phenylpropanoid compound that is highly toxic to RKNs and pinewood nematodes (Oka, 2001;Kong et al, 2007).…”
Section: Lignin Accumulation As a Defense Against Ppnsmentioning
confidence: 99%